Penerapan Sound System dalam Ibadah Liturgi Minggu di HKI Perumnas Pagar Beringin Sipoholon Tapanuli Utara - Monang Asi Sianturi; Lamtulus Nainggolan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to determine the role of the Sound System in the liturgy of Sunday services at church. The sound system in a church is an electronic device that is used to amplify and regulate sound so that it can be heard clearly by the congregation. The method used in this research is descriptive qualitative method. The stages of research implementation were carried out through observation, application, interviews and documentation. The object of this research was carried out at the HKI Perumnas Pagar Beringin Sipoholon, North Tapanuli church. In the research process, the author carried out research on the sound system in the church for 3 months, namely from June to September 2024. The stages carried out by the researcher to regulate the role of the Sound System so that it functions according to its use are: recognizing the devices in the Sound System, finding problems with the Sound System , organizing and arranging the Sound System according to its role. The results of this research show that the implementation of the use of the Sound System at the HKI Perumnas Pagar Beringin Sipoholon North Tapanuli church is functioning and can be heard clearly and well, where previously the sound system often occurred storing or buzzing. Based on this research, the author suggests that sound system operators in churches prepare sound system equipment before the Sunday worship program begins.